2005
DOI: 10.1007/s11373-005-9038-6
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells are superior to angiogenic growth factor genes for improving myocardial performance in the mouse model of acute myocardial infarction

Abstract: SummaryBoth cell therapy and angiogenic growth factor gene therapy have been applied to animal studies and clinical trials. Little is known about the direct comparison between cell therapy and angiogenic growth factor gene therapy. The goal of this study was to compare the effects of human bone marrow-derived mesenchymal stem cells (hMSCs) transplantation and injection of angiogenic growth factor genes in a model of acute myocardial infarction in mice. The hMSCs were obtained from adult human bone marrow and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…The effects on MAPK signaling were not through elements of the feedback loop as previously reported, 18 but rather through the upstream regulators of MAPK signaling such as angiopoietin 1 and midkine, which are upregulated in cells with chondrogenic potential. These transcripts may have a role not only in the maintenance of the chondrogenic potential but also in the overall physiology of hMSCs; angiopoietin 1 has been implicated in the paracrine tissue repair activity displayed by MSCs [45][46][47] and as an antiapoptotic factor 48 ; secreted frizzledrelated protein 1 has also been reported to play a role in the tissue repair activity of MSCs 49,50 and in controlling osteogenic differentiation. [51][52][53] Additionally, a recent report indicates that six transmembrane epithelial antigen of the prostate 1, also upregulated in cells with chondrogenic potential, may be a marker for MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The effects on MAPK signaling were not through elements of the feedback loop as previously reported, 18 but rather through the upstream regulators of MAPK signaling such as angiopoietin 1 and midkine, which are upregulated in cells with chondrogenic potential. These transcripts may have a role not only in the maintenance of the chondrogenic potential but also in the overall physiology of hMSCs; angiopoietin 1 has been implicated in the paracrine tissue repair activity displayed by MSCs [45][46][47] and as an antiapoptotic factor 48 ; secreted frizzledrelated protein 1 has also been reported to play a role in the tissue repair activity of MSCs 49,50 and in controlling osteogenic differentiation. [51][52][53] Additionally, a recent report indicates that six transmembrane epithelial antigen of the prostate 1, also upregulated in cells with chondrogenic potential, may be a marker for MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that in bone marrow-derived mononuclear cell-treated hearts as opposed to saline-treated hearts, the expression of repairrelated cytokines such as transforming growth factor (TGF)-b, a mediator stimulating collagen synthesis, were down-regulated and this is likely to contribute to the improved LV function as well as reduction in scar tissue [15]. However, the improvement in cardiac function may be ascribed to the self-renewal ability of MSCs and parasecretion of growth factors, in addition to prevention of apoptosis in ischemic myocardium [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms by which MSCs promotes tissue repair after ischemia, is through the process of neovascularization mainly because MSCs produce angiogenic cytokines including VEGF (Kinnaird et al 2004;Kinnaird et al 2004;Ma et al 2005;Tang et al 2005;Zhang et al 2005) and also because of their ability to differentiate into ECs and SMCs (Kinnaird et al 2004;Kinnaird et al 2004;Silva et al 2005). MSCs have to been reported to be superior to angiogenic growth factor genes for improving myocardial performance in the mouse model of acute myocardial infarction (Shyu et al 2006). To date two clinical trials have assessed the therapeutic potential of MSCs for MI.…”
Section: Cell Therapy For Angiogenesis For Cadmentioning
confidence: 99%